Curbing attrition rate in open and distance education in Nigeria: e-counselling as a panacea (2018)
Open and Distance Education (ODE) has grown into an important strategy in resolving problems of access to education in Nigeria. However, despite the expanding growth of ODE and its benefits, it is documented that students who enroll with OD institutions drop out of school due to isolation and disconnectedness. Attrition in ODE has become a great concern in Nigeria because student retention is an important factor in accelerating human capital formation for national development in a global knowledge economy. This paper postulates that e-counselling holds the potential to provide high-quality learner support services and it is positioned to serve as a viable alternative source of help when traditional face to face psychotherapy is not accessible to OD learners.